Mosaic of Translation Teaching: Textual Competence - Iļinska, Larisa; Ivanova, Oksana; Ivanova, Diana (Research in Language, 2025)
The present study is based on the interrelation of translation studies, pedagogy and technology in order to develop students’ textual competence by identifying efficient teaching practices in translator training. Textual competence involves also the understanding and application of various sign systems in contemporary digital texts for meaning representation, thus underlying the transdisciplinary status of Translation Studies as its scope of research has been expanded to cognitive science, neurolinguistics, psycholinguistics, information and communication technologies, computational linguistics, and information processing. The constant search for novel approaches to text analysis and the continuous improvement of the existing teaching strategies are necessary to develop students’ ability to effectively decode and convey meaning within a required context. Nowadays development of textual competence is mostly based on the improvement of such skills of students as professional competence and special text analysis to be able to decode meaning at different levels. The authors present a mosaic of teaching activities that are proposed taking into account skills and abilities that translation students need to develop from the perspective of continuously changing modes of communication. The research findings can serve as the source of inspiration for developing study modules within such study courses as Text Analysis Methods, Stylistics and Editing in the framework of the theory of translation.